The Role of Serum Uric Acid as a Biomarker for Early Detection of Metabolic Syndrome in Middle-Aged Pakistani Adults: A Cross-Sectional Study - Shafaq Nazia, Arshad Ali, Faroz Khan, Muskan Lohana, Bedarbakhat Khan, Tariq Hussain (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Metabolic syndrome (MetS) is the collection of interrelated metabolic abnormalities, including central obesity, hypertension, dyslipidemia, and hyperglycemia, that together increase the risk of cardiovascular disease and type 2 diabetes. The traditional serum uric acid (SUA) marker for gout has recently been implicated in MetS development. However, despite growing international data, no research has been done in the Pakistani population to investigate this association. Aims and Objectives: The objective of the study was to assess the association between serum uric acid levels and metabolic syndrome in middle aged adults visiting tertiary care hospitals of Pakistan and to determine the gender distribution and correlation of SUA with each component of MetS as well. Methodology: It was a cross-sectional observational study in Liaquat University Hospital, Hyderabad/Jamshoro, from July 2022 to June 2023. There were 120 adults aged 40–60 years enrolled. Anthropometric measurements, blood pressure, fasting glucose, lipid profiles, and serum uric acid levels were assessed. NCEP ATP III criteria were used to define metabolic syndrome. SPSS version 26 was used to analyze data with the application of t-tests and Pearson correlation analysis. Results: This was found in 56.7% of the participants. Mean serum uric acid was significantly higher in the MetS group (6.8 ± 1.1 mg/dL) than in non non-MetS group (5.3 ± 1.0 mg/dL, p < 0.001). A positive correlation was seen between serum uric acid and waist circumference, systolic blood pressure, and triglyceride, and a negative correlation with HDL cholesterol. Gender-specific analysis showed consistent associations. Conclusion: Serum uric acid is strongly associated with metabolic syndrome and the degree of severity. SUA measurement could be used to early identify persons at metabolic risk in Pakistan. Keywords: serum uric acid, metabolic syndrome, middle-aged adults, Pakistan, hyperuricemia, cardiovascular risk